Cloning of vacll into pnmn013: development of a recombinant bcg vaccine against tuberculosis - Ramli, Siti Nur Rasyidah Md (2004)
In previous study, the Vacll gene has been constructed through the technique of assembly PCR and has been cloned into pKK to produce surface display vaccine candidate (pTMSinakVacll). Vacll gene is a synthetic gene consists of selected T cell epitopes of Mycobacterium tuberculosis (MTB) genes namely ESAT6, MTP40, 38kD and MPT64. In this study, Vacll gene was cloned into pNMN013 for development of a recombinant BCG vaccine. PCR was used for the amplification of the gene DNA from pTMSinakVacll. The PCR products (Vacll gene) were visualized directly on agarose gel. The PCR product was first cloned into pTOPO vector. The PCR product were also digested with Nhel and Ndel and cloned into Nhel and Ndel digested pNMN013. The plasmids were transformed into E.coli. There were some colonies grown on the agar plate. Finally, the colonies were screened using PCR technique and restriction enzyme analysis. But after the screening procedures were done no expected recombinant plasmid were obtained.